THE EFFECT OF BITTER TUAK DRINK TYPES ON THE ROUGHNESS OF HEAT-CURED ACRYLIC RESIN SURFACES - Nur Aedah Ahmad Rani; Firman Firman; Aisyah AR (Media Ilmiah Kesehatan Indonesia, 2026)
Heat-cured acrylic resin is widely used as a denture base material due to its favorable esthetics, biocompatibility, and ease of manipulation. However, this material has water absorption properties, and exposure to acidic and alcoholic solutions may affect its surface roughness. Bitter palm wine derived from aren, lontar, and nipah contains alcohol and has an acidic nature that may interact with the surface of acrylic resin. This study aimed to analyze the effect of immersion in three types of bitter palm wine on the surface roughness of heat-cured acrylic resin denture bases. This laboratory experimental study employed a pretest–posttest with control group design. A total of 24 heat-cured acrylic resin plates measuring 30 × 10 × 2 mm were divided into four groups: distilled water as the control group and bitter palm wine from aren, lontar, and nipah as treatment groups. Surface roughness was measured before and after immersion using a Surface Roughness Tester (SRT). Data were analyzed using the One Way ANOVA and LSD tests. Surface roughness values varied among the immersion groups. However, statistical analysis showed no significant difference between groups (p = 0.778). Descriptively, immersion in bitter palm wine showed a tendency to alter the surface roughness of heat-cured acrylic resin, although the effect was not statistically significant.